Round The Savannah - (:unkn) unknown (Wilsons Ltd., Trinidad, 2009)
A view of someone standing in the road that goes alongside the Pitch Walk of the Queen's Park Savannah.
Colour: Black and White; Style: Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--Port of Spain; [1909]; Roads--Trinidad and Tobago; Trees--Trinidad and Tobago; Roads--Guard fences; Fences--Trinidad and Tobago; Parks--Trinidad and Tobago; Persons--Trinidad and Tobago; Electric lines--Trinidad and Tobago; Overhead electric lines--Trinidad and Tobago; Electric power distribution--Trinidad and Tobago; Queen's Park Savannah (Port of Spain); Pitch Walk, The